2021
DOI: 10.1088/1361-6501/abef3b
|View full text |Cite
|
Sign up to set email alerts
|

Development of compact electronic noses: a review

Abstract: An electronic nose (e-nose) is a measuring instrument that mimics human olfaction and outputs ‘fingerprint’ information of mixed gases or odors. Generally speaking, an e-nose is mainly composed of two parts: a gas sensing system (gas sensor arrays, gas transmission paths) and an information processing system (microprocessor and related hardware, pattern recognition algorithms). It has been more than 30 years since the e-nose concept was introduced in the 1980s. Since then, e-noses have evolved from being large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 208 publications
0
50
0
Order By: Relevance
“…One area in which these systems have pushed to increase commercial potential is through miniaturization and modularity. There have been efforts with several of the methods presented here to develop compact standalone devices that rival their bulkier counterparts in terms of performance [16,47,[162][163][164][165][166]. We believe that cloud computing may be a key element to the success of these endeavors.…”
Section: Considerations and Future Perspectivesmentioning
confidence: 99%
“…One area in which these systems have pushed to increase commercial potential is through miniaturization and modularity. There have been efforts with several of the methods presented here to develop compact standalone devices that rival their bulkier counterparts in terms of performance [16,47,[162][163][164][165][166]. We believe that cloud computing may be a key element to the success of these endeavors.…”
Section: Considerations and Future Perspectivesmentioning
confidence: 99%
“…Sensing devices, designed for the classification of complex gaseous mixtures, are very often called electronic noses [16]. The working principle of these instruments is inspired by the sensing mechanism of mammal senses.…”
Section: Beehive Air Measurement For Beekeepingmentioning
confidence: 99%
“…Proposed constructions, applications, or limitations and challenges of e-noses designed for studies of fungal, bacterial, and viral infections can be found in several review papers [ 39 , 40 , 41 , 42 , 43 ]. Electronic noses have also found applications in cheese ripening analysis [ 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%